Antioxidant soft high-resilience polyurethane sponge as well as preparation method and application thereof
By introducing isocyanate-grafted polysiloxane into polyurethane foam, the brittleness problem caused by ether bond oxidation was solved, the oxidation resistance and mechanical properties of polyurethane foam were improved, and the requirements of the automotive interior and furniture industries were met.
Patent Information
- Application Number
- CN202511301445.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-11-21
AI Technical Summary
Existing polyurethane foams are susceptible to heat, oxygen, and light during transportation, storage, and foaming. Oxidation of ether bonds increases the material's brittleness and reduces its resilience. The oxidation of polyether segments cannot be effectively addressed, and the requirements for oxidation resistance and tear resistance in the automotive interior and furniture industries cannot be met.
Polyurethane foam is synthesized using polyisocyanates containing polysiloxane segments. By grafting polysiloxanes with isocyanates and reacting them with aromatic isocyanates, polysiloxane segments of different lengths are introduced to improve the antioxidant effect while maintaining tear resistance and flexibility.
This improved the antioxidant effect of polyurethane foam, maintained its tear resistance and resilience, and improved the overall mechanical properties and stability of the material.
Smart Images

Figure BDA0005592963320000021 
Figure BDA0005592963320000051 
Figure BDA0005592963320000052
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane foam technology, specifically relating to antioxidant soft high-resilience polyurethane foam, its preparation method and application. Background Technology
[0002] Polyurethane foam is a type of flexible polyurethane foam produced through a foaming process from raw materials such as polyether polyols and polyisocyanates. It features a porous honeycomb structure, is lightweight, highly elastic, and exhibits excellent water resistance. It also possesses superior cushioning, flexibility, and plasticity, making it widely used in automotive parts such as seat cushions, armrests, headrests, and interior panels, as well as furniture such as sofas, armrests, mattresses, and seat cushions. However, due to the indispensable polyether segments that provide flexibility and plasticity in its raw materials, it is susceptible to the effects of heat, oxygen, and light during transportation, storage, and foaming. Hydrogen atoms on adjacent alkyl groups of the ether bonds can easily detach, forming carbon free radicals, which gradually develop into carbon-oxygen free radicals and peroxides, ultimately producing small-molecule aldehydes. These substances pose various health risks, ranging from acute irritation to long-term carcinogenicity. Furthermore, the oxidative degradation of the ether segments also damages the soft segment structure of the polyurethane foam material, increasing its brittleness and resulting in a rough feel, significantly reduced mechanical properties, particularly decreased resilience and easy tearing.
[0003] Currently, the conventional solution is to add antioxidants and light stabilizers to the polyurethane foam formulation to slow down the oxidation rate of polyurethane segments. However, adding antioxidants and other additives can only temporarily delay the oxidation process and cannot fundamentally solve the problem of easy oxidation of polyether segments. With industry development, updated standards, and increasing consumer demands, the automotive interior and furniture industries are also raising their requirements for the oxidation resistance, tear resistance, resilience, and other mechanical properties of polyurethane foam products. Therefore, it is necessary to further improve the performance of polyurethane foam by starting with molecular structure design. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to use polyisocyanates containing polysiloxane segments to synthesize polyurethane foam, thereby improving the tear resistance, flexibility, resilience and oxidation resistance of polyurethane foam.
[0005] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows:
[0006] In the first aspect, a polyurethane foam, the raw materials of which include: polyether polyol, aromatic isocyanate, isocyanate-grafted polysiloxane, catalyst, and water.
[0007] The polyether polyol contains polyoxyethylene or polyoxypropylene segments, and the number of hydroxyl groups in each molecule of polyether polyol is ≥2.
[0008] Preferably, the polyether polyol contains a polyether triol, wherein the number-average molecular weight of the polyether triol is between 1000 and 5000 g / mol;
[0009] The aromatic isocyanate is selected from one or more combinations of monomeric MDI, polymeric MDI, 2,4-TDI, 2,6-TDI, PDI, NDI, and their dimers and trimers;
[0010] The general structural formula of the isocyanate-grafted polysiloxane is:
[0011]
[0012] Wherein, R1, R2, and R4 may be the same or different, and are selected from hydrocarbon groups with 1 to 4 carbon atoms, or phenyl groups; n is a positive integer greater than or equal to 1; a is a positive integer greater than or equal to 1; b is a positive integer greater than or equal to 2;
[0013] Preferably, R1, R2, and R4 are the same, all being methyl groups;
[0014] The structure of R3 is -Alk1-Ar-Alk2-NCO or -Alk1-A-Alk2-NCO, wherein Alk1 is selected from a straight-chain hydrocarbon group, branched hydrocarbon group, or cyclic hydrocarbon group with 1 to 12 carbon atoms; Alk2 is selected from a straight-chain hydrocarbon group, branched hydrocarbon group, or cyclic hydrocarbon group with 1 to 20 carbon atoms; Ar is selected from aromatic hydrocarbons, heterocyclic aromatic hydrocarbons, or their derivatives with 3 to 18 carbon atoms; and A is selected from ether bond -O-, ketone bond -(C=O)-, ester bond -(C=O)-O-, carbamate bond -NH-(C=O)-O-, or urea bond -NH-(C=O)-NH-.
[0015] Preferably, Alk1 is selected from straight-chain hydrocarbon groups, branched hydrocarbon groups, or cyclic hydrocarbon groups with 1 to 6 carbon atoms;
[0016] Preferably, Alk2 is selected from straight-chain hydrocarbon groups, branched hydrocarbon groups, or cyclic hydrocarbon groups with 1 to 14 carbon atoms;
[0017] Preferably, A is selected from a carbamate bond;
[0018] Preferably, the structure of R3 is selected from... Any one of them.
[0019] The catalyst is selected from one or a combination of two of the following: tertiary amine catalysts and organobismuth catalysts;
[0020] The organic bismuth catalyst is composed of bismuth ions (Bi). 3+ Compounds formed by the combination of organic acids or organic alcohol amine ligands;
[0021] Preferably, the tertiary amine catalyst is selected from one or more combinations of DABCO NE300, DABCO NE1050 and DABCO NE1070;
[0022] Preferably, the organic bismuth catalyst is selected from one or more combinations of bismuth isooctanoate, bismuth neodecanoate, bismuth naphthenate, and tris(dimethylaminoethoxy)bismuth.
[0023] Further optimization involves selecting a combination of tertiary amine catalysts and organobismuth catalysts.
[0024] Preferably, the water is selected from deionized water, and the standard for deionized water meets the Class II or Class I water standard in GB / T 6682-2008.
[0025] Preferably, the raw material for the polyurethane foam includes a polyether pore-opening agent, wherein the polyether pore-opening agent is a non-silicone pore-opening agent;
[0026] Preferably, the non-silicone pore-opening agent is selected from any one of polymeric polyols (POP) or grafted polyethers;
[0027] Preferably, the raw material of the polyurethane foam includes an antioxidant, which is selected from one or more combinations of Irgastab PUR 55, Irgastab PUR 67, Irgastab PUR 68, Irgastab PUR 70 and Irgastab PUR 71.
[0028] Preferably, the raw material for the polyurethane foam includes a crosslinking agent selected from one or more combinations of diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine and 4,4'-bis-sec-butylaminodiphenylmethane.
[0029] Further, the raw materials of the polyurethane foam are in the following proportions by weight: 90-120 parts by weight of polyether polyol, 55-70 parts by weight of aromatic isocyanate, 5-20 parts by weight of isocyanate-grafted polysiloxane, 0.5-3 parts by weight of polyether pore-opening agent, 2-8 parts by weight of antioxidant, 0.5-3 parts by weight of crosslinking agent, 1-3 parts by weight of catalyst, and 1-5 parts by weight of water.
[0030] Preferably, the composition comprises 90-110 parts by weight of polyether polyol, 60-70 parts by weight of aromatic isocyanate, 5-15 parts by weight of isocyanate-grafted polysiloxane, 0.5-2 parts by weight of polyether pore-opening agent, 3-6 parts by weight of antioxidant, 0.5-2 parts by weight of crosslinking agent, 1-3 parts by weight of catalyst, and 1-5 parts by weight of water.
[0031] Preferably, the polyether triol content in the raw material of the polyurethane foam is 80-90 parts by weight.
[0032] Secondly, the preparation method of the polyurethane foam described above includes: pre-mixing polyether polyol and antioxidant to obtain a polyether polyol mixture; adding other components except isocyanate to the polyether polyol mixture and mixing them together; then adding isocyanate-grafted polysiloxane and mixing; finally adding isocyanate components and mixing; after stirring, pouring the mixture into a mold and closing the mold; and then opening the mold to obtain the polyurethane foam.
[0033] Preferably, the polyether polyol and antioxidant in the prescribed amounts are premixed for 10-60 minutes to obtain a polyether polyol mixture;
[0034] Preferably, the components other than isocyanate are added together with the polyether polyol mixture and mixed for 30-90 seconds;
[0035] Preferably, the mixing time for adding isocyanate-grafted polysiloxane is 10-30 seconds;
[0036] Preferably, the isocyanate component is added last and mixed, stirred for 3-15 seconds, then poured into the mold and closed.
[0037] Preferably, the polyurethane foam is poured into a mold and closed. After 5-30 minutes, the mold is opened to obtain the polyurethane foam.
[0038] Thirdly, the above-mentioned polyurethane foam is used in mattresses, car seat cushions, and thermal and sound insulation materials.
[0039] The beneficial effects of this invention are as follows: By introducing isocyanate-grafted polysiloxane components into polyurethane foam, and through the reaction of isocyanate-grafted polysiloxane with aromatic isocyanate and polyether polyol, polysiloxane segments of different lengths are introduced, achieving better antioxidant effects while maintaining the tear resistance, flexibility, and resilience of the polyurethane foam. Furthermore, it has been found that introducing isocyanate with shorter polysiloxane segments can improve the tear resistance of the polyurethane foam while ensuring flexibility and resilience. Detailed Implementation
[0040] The present application will be further described in detail below with reference to the embodiments and examples. It should be understood that these embodiments and examples are only for illustrating the present application and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the disclosure of the present application more thorough and complete. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. In addition, numerous specific details are set forth in the following description in order to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0041] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0042] Unless otherwise specified, the experimental conditions used in the examples are generally in accordance with conventional conditions in the art or the conditions recommended by the reagent company. Unless otherwise specified, the materials and reagents used in the examples can be purchased commercially.
[0043] Example 1
[0044] The synthesis of bifunctional isocyanate-terminated polysiloxane monomers was carried out using 1,1,3,3-tetramethyldisiloxane and 3-isopropyl-dimethylbenzyl isocyanate as starting materials. 102.64 g (0.51 mol) of 3-isopropyl-dimethylbenzyl isocyanate and 30 mL of xylene were added to a three-necked flask. The mixture was heated to 95 °C with stirring, and then 33.58 g (0.25 mol) of 1,1,3,3-tetramethyldisiloxane, 0.12 g of Karstedt catalyst, and 20 mL of xylene were added dropwise. The reaction temperature was maintained at 95 °C, and the addition was completed over 2 hours. The reaction was then maintained at this temperature for 3 hours. The reaction was then stopped, cooled, and the solvent and unreacted monomers were removed by vacuum distillation at 0.01 MPa and 70 °C to obtain the bifunctional isocyanate-terminated polysiloxane monomers.
[0045] Structural characterization of the product, 1H NMR spectroscopy. 1¹H-NMR (400MHz, solvent CDCl₃): δ 7.08–7.29 (4H, 7.22 (ddd, J = 8.01, 7.91, 0.53 Hz), 7.14 (ddd, J = 8.01, 2.13, 1.54 Hz)), 6.96 (2H, ddd, J = 7.91, 2.13, 1.04 Hz), 6.36 (2H, ddd, J = 1.54, 1.04, 0. 53Hz),3.06(2H,ddq,J=10.07,10.07,6.97Hz),1.46-1.56(12H,1.51(s),1.51(s)),1.13( 6H, d, J = 6.97Hz), 0.77-0.89 (4H, 0.83 (d, J = 10.07Hz), 0.83 (d, J = 10.07Hz)), 0.03 (12H, s).
[0046] 1H NMR spectrum 13 C-NMR (101 MHz, solvent CDCl3): δ 148.50 (2C), 131.60 (2C), 130.10 (2C), 129.56 (2C), 129.35 (2C), 129.00 (2C), 127.60 (2C), 88.30 (2C), 39.58 (2C), 27.00 (2C), 24.56 (2C), 22.00 (2C), 21.15 (2C), 0.60 (4C).
[0047] The corresponding reaction formula is:
[0048]
[0049] Example 2
[0050] The synthesis of bifunctional isocyanate-terminated polysiloxane monomers involved using hydrogen-terminated silicone oil (0.17% hydrogen content, Herun New Materials) with an average molecular weight of 1200 and 3-isopropyl-dimethylbenzyl isocyanate as raw materials. 104.65 g (0.52 mol) of 3-isopropyl-dimethylbenzyl isocyanate and 30 mL of xylene were added to a three-necked flask. The mixture was heated to 95 °C with stirring, and a mixture of 150 g (0.255 mol Si-H) of hydrogen-terminated silicone oil, 0.18 g of Karstedt catalyst, and 60 mL of xylene was added dropwise. The reaction temperature was maintained at 95 °C, and the addition was completed over 3 hours. The reaction was then maintained at this temperature for another 3 hours. The reaction was subsequently stopped, cooled, and the solvent and unreacted monomer were removed by vacuum distillation at 0.01 MPa and 70 °C to obtain the bifunctional isocyanate-terminated polysiloxane monomer.
[0051] The corresponding reaction formula is:
[0052]
[0053] Example 3
[0054] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 1.4 parts by weight of polyether cell opener K340 (BASF); 62.5 parts by weight of aromatic isocyanate TDI-80; 8 parts by weight of difunctional isocyanate-terminated polysiloxane monomer prepared in Example 1; 5 parts by weight of antioxidant Irgastab PUR-70; 1.2 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; 0.6 parts by weight of catalyst DABCO NE1050; 0.5 parts by weight of catalyst bismuth neodecanoate; and 3.8 parts by weight of deionized water.
[0055] Preparation method of polyurethane foam: Add the formulated amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulation components except isocyanate to the beaker and mix for 55 seconds. Then add the formulated amount of the bifunctional isocyanate-terminated polysiloxane monomer prepared in Example 1 and mix with the above components for 15 seconds. Then add the formulated amount of TDI-80 and mix with the above components for 5 seconds. Pour into a square mold, close the mold, and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours (temperature 23±2℃, humidity 50±5℃) for curing, and then conduct subsequent performance tests.
[0056] Example 4
[0057] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 1.3 parts by weight of polyether cell opener K340 (BASF); 63 parts by weight of aromatic isocyanate TDI-80; 10.5 parts by weight of difunctional isocyanate-terminated polysiloxane monomer prepared in Example 2; 5 parts by weight of antioxidant Irgastab PUR-70; 1.2 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; 0.6 parts by weight of catalyst DABCO NE1050; 0.5 parts by weight of catalyst bismuth neodecanoate; and 3.6 parts by weight of deionized water.
[0058] Preparation method of polyurethane foam: Add the formulated amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulation components except isocyanate to the beaker and mix for 55 seconds. Then add the formulated amount of the bifunctional isocyanate-terminated polysiloxane monomer prepared in Example 2 and mix with the above components for 15 seconds. Then add the formulated amount of TDI-80 and mix with the above components for 15 seconds. Pour into a square mold, close the mold, and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours to mature (temperature 23±2℃, humidity 50±5℃) and then conduct subsequent performance tests.
[0059] Example 5
[0060] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 1.4 parts by weight of polyether cell opener K340 (BASF); 64.5 parts by weight of aromatic isocyanate TDI-80; 11 parts by weight of terminal isocyanate polysiloxane prepolymer Silmer NCO Di-50 (SILTECH CORPORATION); 15 parts by weight of antioxidant IrgastabPUR-7; 1.2 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; 0.6 parts by weight of catalyst DABCO NE1050; 0.5 parts by weight of catalyst bismuth neodecanoate; and 3.5 parts by weight of deionized water.
[0061] The structural formula of Silmer NCO Di-50 is shown below. The number-average molecular weight of Silmer NCO Di-50 is 4300 g / mol.
[0062]
[0063] Preparation method of polyurethane foam: Add the formulated amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulated components except isocyanate to the beaker and mix for 55 seconds. Then add the formulated amount of Silmer NCO Di-50 and mix with the above components for 25 seconds. Then add the formulated amount of TDI-80 and mix with the above components for 5 seconds. Pour into a square mold, close the mold, and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours to cure (temperature 23±2℃, humidity 50±5℃) and then conduct subsequent performance tests.
[0064] Example 6
[0065] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 1.4 parts by weight of polyether cell opener K340 (BASF); 64.5 parts by weight of aromatic isocyanate TDI-80; 9.5 parts by weight of side-isocyanate polysiloxane prepolymer Silmer NCO C-50 (SILTECH CORPORATION); 15 parts by weight of antioxidant IrgastabPUR-7; 0.8 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; 0.6 parts by weight of catalyst DABCO NE1050; 0.5 parts by weight of catalyst bismuth neodecanoate; and 3.4 parts by weight of deionized water.
[0066] The structural formula of Silmer NCO C-50 is shown below. The number-average molecular weight of Silmer NCO C-50 is 12400 g / mol.
[0067]
[0068] Preparation method of polyurethane foam: Add the prescribed amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulation components except isocyanate to the beaker and mix for 55 seconds. Then add the prescribed amount of Silmer NCO C-50 and mix with the above components for 25 seconds. Then add the prescribed amount of TDI-80 and mix with the above components for 5 seconds. Pour into a square mold, close the mold, and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours to cure (temperature 23±2℃, humidity 50±5℃) before subsequent performance testing.
[0069] Comparative Example 1
[0070] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 1.4 parts by weight of polyether cell opener K340 (BASF); 62.5 parts by weight of aromatic isocyanate TDI-80; 9.5 parts by weight of aliphatic isocyanate 4,4-diisocyanate dicyclohexylmethane HMDI; 5 parts by weight of antioxidant Irgastab PUR-70; 0.8 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; 0.6 parts by weight of catalyst DABCO NE1050; 0.5 parts by weight of catalyst bismuth neodecanoate; and 3.4 parts by weight of deionized water.
[0071] Preparation method of polyurethane foam: Add the prescribed amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulation components except isocyanate to the beaker and mix for 55 seconds. Then add the prescribed amount of TDI-80 and HMDI, stir for 5 seconds and pour into a square mold. Close the mold and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours to mature (temperature 23±2℃, humidity 50±5℃) and then conduct subsequent performance tests.
[0072] Comparative Example 2
[0073] Polyurethane foam was prepared using the following raw materials in parts by weight: 85 parts by weight of polyether triol LE-335D (hydroxyl value 48.5 mg KOH / g, Eastman Chemical) with an average molecular weight of 3500; 15 parts by weight of polyether polyol SP22-40 (CNOOC Shell Petrochemical); 8 parts by weight of hydroxypropyl dimethyl silicone oil IOTA 2030 (average molecular weight 3000 g / mol, Anhui Aiyota Silicone Oil); 1.4 parts by weight of polyether pore-opening agent K340 (BASF); 64 parts by weight of aromatic isocyanate TDI-80; 10.5 parts by weight of aliphatic isocyanate 4,4-diisocyanate dicyclohexylmethane HMDI; 5 parts by weight of antioxidant Irgastab PUR-71; 0.8 parts by weight of crosslinking agent diisopropanolamine; 1.0 part by weight of catalyst DABCO NE1070; 0.2 parts by weight of catalyst DABCO NE300; and catalyst DABCO... NE1050 0.6 parts by mass, catalyst bismuth neodecanoate 0.5 parts by mass, deionized water 3.4 parts by mass.
[0074] The structural formula of the double-ended hydroxypropyl silicone oil IOTA 2030 is shown below;
[0075]
[0076] Preparation method of polyurethane foam: Add the prescribed amount of polyether triol, polyether polyol and antioxidant to a dry beaker and mix for 40 minutes. Then add the mixture and the above-mentioned formulation components except isocyanate to the beaker and mix for 55 seconds. Then add the prescribed amount of TDI-80 and HMDI, stir for 5 seconds and pour into a square mold. Close the mold and after 10 minutes, open the mold and take out the square foam. Place it in a constant temperature and humidity environment for 24 hours to mature (temperature 23±2℃, humidity 50±5℃) and then conduct subsequent performance tests.
[0077] Comparative Example 3
[0078] The mass fractions of each component of the polyurethane foam are the same as in Example 5.
[0079] The preparation method of polyurethane foam in Comparative Example 3 differs from that in Example 5. The isocyanate components, including Silmer NCO Di-50 and TDI-80, are added to the mixture of other components in the prescribed amount. After mixing for 10 seconds, the mixture is poured into a square mold, the mold is closed, and after 10 minutes, the mold is opened and the square foam is removed. It is then placed in a constant temperature and humidity environment for 24 hours to mature (temperature 23±2℃, humidity 50±5℃) before subsequent performance testing.
[0080] Performance testing section:
[0081] The tensile strength, elongation at break, and drop ball rebound of the polyurethane foams prepared in Examples 3-6 and Comparative Examples 1-3 were measured according to the standard ASTM D 3574-17.
[0082] For the aging resistance test, refer to the high-pressure steam aging J2 method in ASTM D 3574-17 standard. Add the test sample to the steam boiler, control the steam boiler temperature at 105±3℃, and continue for 3 hours to end the experiment. After the test sample is placed at room temperature to cool for 2 hours, test the tensile strength, elongation at break and drop ball rebound rate after aging.
[0083] Referring to the dry heat aging K method in ASTM D 3574-17, the test sample was placed in an air circulation chamber, the temperature was controlled at 140±2℃, and the experiment was ended after 22 hours. The test sample was then placed at room temperature to cool for 2 hours before testing the tensile strength, elongation at break and rate of change of drop ball rebound after aging.
[0084] The foaming activity test was conducted by measuring the pore-breaking force. The formulated amounts of polyether triol, polyether polyol, and antioxidant were added to a dry beaker and mixed for 40 minutes. Then, the components of the formulations described in Examples 3-6 and Comparative Examples 1-3, excluding isocyanate, were weighed into the beaker and mixed for 55 seconds. Next, the formulated amounts of isocyanate (TDI-80 or TDI-80 and HMDI) were added, and after stirring for 5 seconds, the mixture was poured into a 5L cylindrical container. Free foaming was then carried out at 25±2℃ and 50±5% RH. After the foaming reaction was complete, the sample was allowed to stand for 30 minutes. A cylindrical sample, including the top skin, was vertically cut from the center of the free foam. A spherical probe was mounted on the moving beam of the UTM testing machine, with the top skin of the polyurethane foam sample horizontally facing the probe. The spherical probe was moved downwards at a speed of 300 mm / min until it contacted and punctured the top skin of the foam. The peak force was read from the force-displacement curve generated on the UTM testing machine; this peak force is the pore-breaking force.
[0085] The test results described above are summarized in Table 1.
[0086] Table 1
[0087]
[0088] As can be seen from the test results in Table 1, Comparative Example 1, which used MDI and TDI-80 alone as isocyanate components, did not introduce polysiloxane segments into the polyurethane foam. The oxidation reaction directly attacked and severed the polyether segments of the polyurethane polymer, leading to a decrease in molecular weight. This directly manifests as increased brittleness in the polyurethane foam material, and a reduction in tensile strength, elongation at break, and drop ball rebound performance.
[0089] Comparative Example 2 introduced polysiloxane segments into the polyurethane polymer. These highly flexible segments increase the degree of microphase separation and segment mobility in the soft segment regions of the polyurethane, making it easier for reactive species such as free radicals to migrate and be captured by the added oxidant, thereby improving the stability of the polyurethane sponge material. However, a drawback is the poor compatibility between the polysiloxane and polyether segments, which can lead to uneven segment distribution during the initial mixing process, resulting in an overall less than ideal antioxidant effect.
[0090] Examples 3-6 are improvements on Comparative Example 2, in which isocyanate functional groups are grafted onto polysiloxane segments. Since isocyanate has high reactivity with hydroxyl groups in the amine / organobismuth catalytic system, it can quickly solidify. Because the polysiloxane segments are incompatible with the polyurethane matrix, they will spontaneously migrate to the material surface and accumulate during the curing process, forming a polysiloxane layer. This stabilizes the foaming process of the polyurethane sponge, forming a dense structure with uniform pores and thick, tough pore walls, reducing the contact area between the material and oxygen or water vapor, and ultimately improving the antioxidant effect of the polyurethane sponge.
[0091] In Example 3, the difunctional isocyanate-terminated polysiloxane monomer prepared in Example 1 was used. Because the polysiloxane segments were significantly shorter, the resulting polyurethane sponge exhibited stronger bubble stability, higher tensile strength, and better durability and tear resistance. Overall, its mechanical properties and flexibility were superior to those of Examples 4-6. The reason for this might be that the isocyanate-grafted polysiloxane segments in Examples 4-6 were longer, resulting in poor compatibility with other components of the polyurethane chain. This led to better antioxidant effects but lower mechanical properties. Example 3 introduced shorter polysiloxane segments into the polyurethane sponge, effectively increasing its tensile strength and thus improving the durability and tear resistance of the sponge product.
[0092] Comparative Example 3 used the same formulation as Example 5, but the isocyanate-grafted polysiloxane and aromatic isocyanate were added simultaneously for mixing and reaction. The reactivity of the two was very different. Due to the electron-withdrawing effect of the aromatic groups, the NCO of the aromatic isocyanate was very active and reacted quickly with the polyol component. However, in the isocyanate-grafted polysiloxane, the NCO was directly linked to a hydrocarbon group. In addition, the polysiloxane itself had a high molecular weight and large steric hindrance, resulting in poor NCO reactivity. As a result, the isocyanate-grafted polysiloxane did not react completely, and therefore the properties of the corresponding polyurethane foam decreased significantly.
[0093] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. Furthermore, it should be understood that after reading the above teachings of this application, those skilled in the art can make various alterations or modifications to this application, and the equivalent forms obtained also fall within the scope of protection of this application. It should also be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. A polyurethane foam, characterized in that, Raw materials include: polyether polyol, aromatic isocyanate, isocyanate-grafted polysiloxane, catalyst, and water; The polyether polyol contains polyoxyethylene or polyoxypropylene segments, and the number of hydroxyl groups in each molecule of polyether polyol is ≥2. The aromatic isocyanate is selected from one or more combinations of monomeric MDI, polymeric MDI, 2,4-TDI, 2,6-TDI, PDI, NDI, and their dimers and trimers; The general structural formula of the isocyanate-grafted polysiloxane is: R1, R2, and R4 can be the same or different, and are selected from hydrocarbon groups with 1 to 4 carbon atoms, or phenyl groups; n is a positive integer greater than or equal to 1; a is a positive integer greater than or equal to 1; b is a positive integer greater than or equal to 2; The structure of R3 is -Alk1-Ar-Alk2-NCO or -Alk1-A-Alk2-NCO, wherein Alk1 is selected from a straight-chain hydrocarbon group, branched hydrocarbon group, or cyclic hydrocarbon group with 1 to 12 carbon atoms; Alk2 is selected from a straight-chain hydrocarbon group, branched hydrocarbon group, or cyclic hydrocarbon group with 1 to 20 carbon atoms; Ar is selected from aromatic hydrocarbons, heterocyclic aromatic hydrocarbons, or their derivatives with 3 to 18 carbon atoms; and A is selected from ether bond -O-, ketone bond -(C=O)-, ester bond -(C=O)-O-, carbamate bond -NH-(C=O)-O-, or urea bond -NH-(C=O)-NH-. The catalyst is selected from one or a combination of two of the following: tertiary amine catalysts and organobismuth catalysts; The organic bismuth catalyst is a compound formed by the combination of bismuth ions with organic acids or organic alcohol amine ligands.
2. The polyurethane foam according to claim 1, characterized in that, The polyether polyol contains polyether triol, and the number average molecular weight of the polyether triol is between 1000 and 5000 g / mol. And / or, the water is selected from deionized water, and the standard for deionized water meets the Class II or Class I water standard in GB / T 6682-2008; And / or, the raw materials for polyurethane foam include polyether pore-opening agents, wherein the polyether pore-opening agents are non-silicone pore-opening agents; And / or, the raw materials of the polyurethane foam include antioxidants, said antioxidants being selected from one or more combinations of Irgastab PUR 55, Irgastab PUR 67, Irgastab PUR 68, Irgastab PUR 70 and Irgastab PUR 71; And / or, the raw materials for the polyurethane foam include a crosslinking agent selected from one or more combinations of diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, and 4,4'-bis-sec-butylaminodiphenylmethane.
3. The polyurethane foam according to claim 2, characterized in that, The non-silicone pore-opening agent is selected from any one of polymeric polyols or grafted polyethers.
4. The polyurethane foam according to claim 1, characterized in that, The tertiary amine catalyst is selected from one or more of DABCONE300, catalyst DABCO NE1050 and catalyst DABCO NE1070.
5. The polyurethane foam according to claim 1, characterized in that, The organic bismuth catalyst is selected from one or more combinations of bismuth isooctanoate, bismuth neodecanoate, bismuth naphthenate, and tris(dimethylaminoethoxy)bismuth.
6. The polyurethane foam according to claim 1, characterized in that, The polyurethane foam comprises the following raw materials in parts by weight: 90-120 parts by weight of polyether polyol, 55-70 parts by weight of aromatic isocyanate, 5-20 parts by weight of isocyanate-grafted polysiloxane, 0.5-3 parts by weight of polyether pore-opening agent, 2-8 parts by weight of antioxidant, 0.5-3 parts by weight of crosslinking agent, 1-3 parts by weight of catalyst, and 1-5 parts by weight of water.
7. The polyurethane foam according to claim 1, characterized in that, The polyurethane foam has the following composition by weight: 90-110 parts by weight of polyether polyol, 60-70 parts by weight of aromatic isocyanate, 5-15 parts by weight of isocyanate-grafted polysiloxane, 0.5-2 parts by weight of polyether pore-opening agent, 3-6 parts by weight of antioxidant, 0.5-2 parts by weight of crosslinking agent, 1-3 parts by weight of catalyst, and 1-5 parts by weight of water. And / or, the content of polyether triol in the raw materials of the polyurethane foam is 80-90 parts by weight.
8. The method for preparing polyurethane foam according to any one of claims 1-7, characterized in that, Polyether polyol and antioxidant are premixed to obtain a polyether polyol mixture. Other components except isocyanate are added to the polyether polyol mixture and mixed together. Then isocyanate-grafted polysiloxane is added and mixed. Finally, isocyanate component is added and mixed. After stirring, the mixture is poured into a mold and the mold is closed. Then the mold is opened to obtain polyurethane foam.
9. The method for preparing polyurethane foam according to claim 8, characterized in that, The polyether polyol and antioxidant in the formula are premixed for 10-60 minutes to obtain a polyether polyol mixture; And / or, add the components other than isocyanate to the polyether polyol mixture and mix for 30-90 seconds; And / or, add isocyanate-grafted polysiloxane and mix for 10-30 seconds; And / or, finally add the isocyanate component and mix, stir for 3-15 seconds and then pour into the mold and close the mold; And / or pour into a mold and close the mold. After 5-30 minutes, open the mold to obtain polyurethane foam.
10. An application characterized in that, Use of the polyurethane foam as described in any one of claims 1-7 in mattresses, car seat cushions, and thermal and sound insulation materials.
Citation Information
Patent Citations
Siloxane-carbamate group fouling-release coating
CN103910853A
Low viscosity moisture cured polymer compositions with tensile and creep properties for Industrial coatings,adhesives and sealant applications
CN105349020A
Isocyanate-free primer and preparation method and application thereof
CN107033768A
Solvent type double-component, high-smoothness vanish composition as well as preparation method and application
CN108192488A
Organosilicon polyurethane foam preparation, polyether grafted polysiloxane polyether block copolymer and preparation method of polyether grafted polysiloxane polyether block copolymer
CN114805730A